Asuhan keperawatan Pada Tn.P Dengan Resiko Perilaku Kekerasan - Putri Nurmala; Sri Nyumirah (AKPER Pasar Rebo, 2019)
Violent behavior is a form of behavior that aims to hurt someone physically and psychologically. This will have a major impact if not addressed. For example people with violent behavior can cause a high risk of injuring themselves, others and the environment. Based on the impact of violent behavior above the role of nurses is needed in carrying out nursing care, namely nurses play a role in the promotive, preventive, curative, and rehabilitative aspects. Nursing care is done by interviews, both to clients, nurses and families, nursing actions are carried out directly on the client with the assistance of nurses. The client experiences violent behavior because the client feels hurt because he is always ridiculed by his neighbors and brother. Nursing diagnoses that can be found on the client are low self-esteem, sensory disturbance perceptions: hallucinations, risk of violent behavior, ineffective therapeutic regimens. Planning has been carried out in accordance with hospital standards. Client nursing evaluations seen in clients are able to control violent behavior by deep breathing and hit the pillow / mattress, taking medication regularly, expressing, asking, and refusing verbally as well as spiritually, namely dhikr and prayer. Another ability that the client achieves is that the client is able to control the hallucinations that arise, and the client is able to increase his self-esteem.